Tracing back seed and pollen flow within the crop-wild Beta vulgaris complex: genetic distinctiveness vs. hot spots of hybridization over a regional scale - Viard, Frédérique; Arnaud, Jean-François; Delescluse, Maxime; Cuguen, Joël (Molecular ecology, 2004)
Hybrids between transgenic crops and wild relatives have been documented successfully in a wide range of cultivated species, having implications on conservation and biosafety management. Nonetheless, the magnitude and frequency of hybridization in the wild is still an open question, in particular when considering several populations at the landscape level. The Beta vulgaris complex provides an excellent biological model to tackle this issue. Weed beets contaminating sugar beet fields are expected to act as a relay between wild populations and crops and from crops‐to‐crops. In one major European sugar beet production area, nine wild populations and 12 weed populations were genetically characterized using cytoplasmic markers specific to the cultivated lines and nuclear microsatellite loci. A tremendous overall genetic differentiation between neighbouring wild and weed populations was depicted. However, genetic admixture analyses at the individual level revealed clear evidence for gene flow between wild and weed populations. In particular, one wild population displayed a high magnitude of nuclear genetic admixture, reinforced by direct seed flow as evidenced by cytoplasmic markers. Altogether, weed beets were shown to act as relay for gene flow between crops to wild populations and crops to crops by pollen and seeds at a landscape level.